Naming the Volyn Football Teams: Tendencies in the 20th – 21st Centuries (Linguostylistic Studies, 2023)
The article elucidates the origin of the unexplored names of Ukrainian football teams organized in the territory of Great Volyn – a historical and geographical region that covers the territory of modern Volyn and Rivne regions, western Zhytomyr, northern Lviv, Ternopil and Khmelnytsky regions, as well as the Ukrainian lands that are now included in other states, such as Kholm region, Pidliashshia region, and Beresteishchyna. The analysis concerns the names of Volyn football teams of the 20th–21st centuries, focusing on the motivation of homonymous and appellative names. The dominant naming trends in different periods of the history of the development of football in Volyn, the influence of various factors on the choice of names have been revealed.There were few football teams in Volyn before the Second World War. Their names were mostly motivated by toponyms, hydronyms, anthroponyms, the nominations of the Ukrainian society life (Derman, Kostopil, Bug, Horyn, Styr, Bohun, Bui-Tur, Prosvita), names of persons, objects, astronomical objects, or abstract names (young man, anchor, comet, hardening, movement, June).In the 1940s and 1980s, football teams names were derived from nominations of all-Union sports associations, ergonyms (Avanhard, Dynamo, Kolos, OBO, OBCHA, Progress, Silmash, Porcelain Factory), names of persons by profession, products of enterprises, and ideological notions (ceramicist, papermaker, textile worker, miner, isotope, bearing, bilshovyk, star). Only a few clubs had names motivated by lexemes with national and cultural semantics (Volyn, Polissia, Horyn, Sluch).After the restoration of Ukrainian independence, many names appeared, formed under the influence of the commercial factors. They are nominations that duplicate the names of organizations that fund football clubs and eclectic names that amalgamate the names of teams with the names of their sponsors (Volyn-Cement, Izotop-RAES, Rud, Sluch-Klasik, Troyanda-Express, Himmash). The study has also identified several original club names (Veres, Zhytychi, Mal).Further research can be conducted to identify trends in the naming of football teams in different Ukrainian regions.
Keywords: names of Volyn’s football teams; a common name (appellative name); onim; motivation; onimization; transonimization